The influence of oxide layer thickness on interface microstructure, bonding strength and wear behavior of silver coating deposited on depleted uranium - Xiaobo Wang; Kunming Yang; Yujia Yang; Shengfa Zhu; Lei Yang; Wenhua Luo; Tao Tang; Yawen Zhao; Qingdong Xu; Dongxu Zhang; Anyi Yin (Results in Surfaces and Interfaces, 2025)
Due to excellent mechanical and physical properties, uranium (U) and its alloys have been widely used in the fields of materials science and nuclear industries but suffer from surface oxidation and good interface bonding with surface protective coatings. In this work, the influence of oxide layer thickness (hUO2+x) on interface microstructure, bonding strength and wear behavior of silver (Ag) coating deposited on depleted uranium (DU) are studied. The results showed that, for comparable DU surface roughness, increasing hUO2+x from <20 nm to ∼155 nm could significantly increase the shear stress of Ag/UO2+x interface accompanied by weakened bonding strength (∼15.2–∼3.5 MPa) via the formation of interface nanoscale voids and micro-cracks. The higher interface bonding with hUO2+x < 40 nm endowed Ag coating with good and stable wear resistance, as evidenced by the low coefficient of friction (COF) of ∼0.26 and nearly no Ag particles in the wear track. The findings may shield on the importance in precisely controlling oxide layer thickness at surface protective coating/U interfaces.